(untitled) (American International Journal of Education and Linguistics Research, 2021)
The advancement of a smart society depends to a large extent on the standard of the higher education system. The fourth Industrial Revolution (FIR), or smart industry, is the trend related to artificial intelligence, changing various aspects of life, especially the education system. The flow of the smart industry, spurring Bangladesh to accept the technologies of the FIR. The drift of FIR will drop a strong impact on our graduates. The smart industry needs the efficiency of Science, Technology, Engineering, and Mathematics (STEM). Mathematics is a scaffold to the next industrial revolution. So, our university education system should be convenient to set up our graduates all around the smart world and overcome the industrial requirements; it is compulsory to adopt Outcome-Based Education (OBE). OBE templates were approved at the 157th meeting of the University Grants Commission of Bangladesh (UGC) on 06 February 2020. Recently, UGC has requested that all universities modify their undergrad educational plans depending on the Outcome-Based Education (OBE) layout. The purpose of this article is to look at the significance of skilled Mathematics alumni for the smart world, and we also examine the challenges of actualizing Outcome-Based Education (OBE).